Microfluidics-enabled rational design for Ag–ZnO nanocomposite films for enhanced photoelectrochemical performance. Issue 4 (12th December 2019) - Jun, Ho Young; Chang, Chih-Hung; Ahn, Kwang-Soon; Ryu, Si Ok; Choi, Chang-Ho
Abstract : A facile and rapid synthetic method to fabricate the Ag–ZnO nanocomposite films with controlled morphology is developed by using microreactor-assisted solution deposition (MASD) process for enhanced photoelectrochemical performance. Abstract : Ag–ZnO nanocomposite films have been widely employed as a promising photocatalyst displaying excellent charge separation and broadband absorption under illumination. Although a variety of synthetic methods have been proposed, the preparation of nanocomposite films with controlled morphology in a single process has been rarely attempted. Here, we introduce a facile and rapid synthetic method to fabricate Ag–ZnO nanocomposite films with controlled morphology by using a microreactor-assisted solution deposition (MASD) process. The nanocomposite film could be formed in a single process within 10 min, which is enabled by rationally designing the MASD process. In addition, by simply tuning in situ growth kinetics of ZnO nanostructures in the process, the morphology of the Ag–ZnO nanocomposite film is varied, including flower- and nanorod-structures. The enhanced photocatalytic activity of the Ag–ZnO nanocomposite film over its pristine ZnO counterpart is demonstrated by performing photoelectrochemical (PEC) measurements.